Battery
By using a combination of fluorovinyl carbonate and a compound shown in the specific formula I in the lithium-ion battery electrolyte, the problem of insufficient stability of the electrolyte interface film is solved, and the excellent performance of the battery under high pressure and high temperature conditions is achieved.
Patent Information
- Application Number
- CN202411742157.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
With the increase in the voltage of lithium-ion battery cells, the interface film formed by conventional electrolytes is insufficient, resulting in increased electrolyte consumption and impedance, which has a negative impact on cycle life.
An electrolyte containing fluorovinyl carbonate (FEC) and a specific compound represented by formula I is used. This compound releases trimethylsilane (TMS) radicals through silane groups to promote the ring opening reaction of FEC, generates a modified fluoropolymer, and improves the stability and conductivity of the interface film.
Form a stable interface film, reduce interface resistance, improve conductivity, reduce the decomposition of the electrolyte, protect the stability of the positive electrode material, and improve the cycling performance and high-temperature storage performance of the battery under high-voltage conditions.
Smart Images

Figure CN119674218A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of material preparation, and in particular, to batteries. Background Art
[0002] As the application fields of lithium-ion batteries continue to expand, the performance requirements of lithium-ion batteries in different application fields vary greatly. Higher energy density is the mainstream demand direction in the current market, and high voltage is the most direct and effective way to increase energy density. However, as the battery cell voltage increases, the interfacial film formed by conventional electrolytes is not stable enough and will continue to decompose, resulting in increased electrolyte consumption and impedance, which has a negative impact on cycle life. Summary of the invention
[0003] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the present application proposes a battery, wherein the electrolyte in the battery of the present application can form a stable interface film with low interface resistance and high conductivity, and the electrolyte is not easy to decompose, which helps to improve the stability of the positive electrode material and reduce its capacity loss, thereby improving the cycle performance and high temperature storage performance of the battery under high voltage conditions.
[0004] The present application provides a battery, wherein the operating voltage of the battery is not less than 4.5V, the battery comprises an electrolyte, and the electrolyte comprises a first component and a second component;
[0005] The first component includes fluoroethylene carbonate (FEC for short);
[0006] The second component includes a compound shown in formula I:
[0007] wherein R1, R2 and R3 are each independently selected from F, C1-C4 alkyl, C2-C4 alkenyl, -OP(=O)F2, -Si(R3)(R4)OP(=O)F2 or -OSi(R3)(R4)OP(=O)F2;
[0008] R3 and R4 are each independently selected from C1-C4 alkyl groups.
[0009] The electrolyte according to the embodiment of the present application can form a stable interface film with low interface resistance and high conductivity. The electrolyte is not easy to decompose, which helps to improve the stability of the positive electrode material and reduce its capacity loss, thereby improving the cycle performance and high temperature storage performance of the battery under high voltage conditions.
[0010] According to an embodiment of the present application, the compound represented by Formula I includes at least one of the compounds having structures represented by Formulas 1 to 9:
[0011]
[0012] According to an embodiment of the present application, based on the total mass of the electrolyte, the mass proportion of the second component is 0.5% to 3%.
[0013] According to an embodiment of the present application, the battery further includes: a positive electrode plate, the positive electrode plate includes a positive electrode active material, and the positive electrode active material includes lithium cobalt oxide.
[0014] According to an embodiment of the present application, based on the total mass of the electrolyte, the mass proportion of the first component is 2% to 10%;
[0015] And / or, the mass ratio of the first component to the second component is (0.67-20):1.
[0016] According to an embodiment of the present application, the electrolyte includes a non-aqueous organic solvent;
[0017] The non-aqueous organic solvent comprises at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate and ethyl butyrate;
[0018] And / or, based on the total mass of the electrolyte, the mass proportion of the non-aqueous solvent is 67% to 89.5%.
[0019] According to an embodiment of the present application, the battery further includes: a positive electrode plate, the positive electrode plate includes a positive electrode active material, and the positive electrode active material includes lithium nickel manganese oxide.
[0020] According to an embodiment of the present application, the operating voltage of the battery is not less than 4.7V.
[0021] According to an embodiment of the present application, based on the total mass of the electrolyte, the mass proportion of the first component is 6% to 30%, preferably 10% to 20%;
[0022] And / or, the mass ratio of the first component to the second component is (2-60):1.
[0023] According to an embodiment of the present application, the electrolyte includes a non-aqueous organic solvent;
[0024] The non-aqueous organic solvent comprises at least one of bisfluoroethylene carbonate, 4-difluoromethylethylene carbonate, 4-trifluoromethylethylene carbonate, 2-fluoroethyl methyl carbonate, 2,2-difluoroethyl methyl carbonate, 2,2,2-trifluoroethyl methyl carbonate, 2-fluoroethyl ethyl carbonate, 2,2-difluoroethyl ethyl carbonate, 2,2,2-trifluoroethyl ethyl carbonate, bis(2-fluoroethyl) carbonate, bis(2,2-difluoroethyl) carbonate and bis(2,2,2-trifluoroethyl) carbonate;
[0025] And / or, based on the total mass of the electrolyte, the mass proportion of the non-aqueous solvent is 47% to 85.5%.
[0026] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. DETAILED DESCRIPTION
[0027] The following is a detailed description of the embodiments of the technical solution of the present application. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0028] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0029] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 listed, and if the maximum range values 3,4 and 5 are listed, the following scope can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers, and the scope limited in this way can be including end values a and b. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0030] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0031] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0032] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0033] The present application provides a battery. According to an embodiment of the present application, the operating voltage of the battery is not less than 4.5V, and the battery includes an electrolyte, and the electrolyte includes a first component and a second component;
[0034] The first component includes fluoroethylene carbonate;
[0035] The second component includes a compound shown in formula I:
[0036] wherein R1, R2 and R3 are each independently selected from F, C1-C4 alkyl, C2-C4 alkenyl, -OP(=O)F2, -Si(R3)(R4)OP(=O)F2 or -OSi(R3)(R4)OP(=O)F2;
[0037] R3 and R4 are each independently selected from C1-C4 alkyl groups.
[0038] The electrolyte according to the embodiment of the present application can form a stable interface film with low interface resistance and high conductivity. The electrolyte is not easy to decompose, which helps to improve the stability of the positive electrode material and reduce its capacity loss, thereby improving the cycle performance and high temperature storage performance of the battery under high voltage conditions.
[0039] The following is a detailed description of the principle by which the present application can achieve the above beneficial effects:
[0040] Compared with conventional cyclic carbonates EC and PC, fluoroethylene carbonate (FEC) has a higher oxidation potential and a lower reduction potential. Therefore, on the one hand, FEC can obtain electrons and be reduced before conventional solvents such as EC / PC to form F-containing organic matter and LiF, which improves the ion conductivity and stability of the interface film. On the other hand, the high oxidation potential of FEC will improve the adaptability of the high-voltage battery system and improve the intrinsic high-voltage stability of the electrolyte, which makes FEC a high-voltage resistant solvent. However, FEC is prone to decomposition reactions under high temperature conditions to generate hydrofluoric acid (HF). HF is a strong acid that can corrode metal parts inside the battery, destroy the structure of the electrode material, increase the internal resistance of the battery, and thus reduce the battery's charge and discharge efficiency and cycle stability. In addition, the generation of HF may also cause the decomposition of the electrolyte, reduce the amount of electrolyte, and affect the long-term cycle performance of the battery.
[0041] Therefore, the high-temperature performance deficiency caused by FEC is synthesized by adding a highly active compound shown in Formula I, wherein the silane group can release trimethylsilane (TMS)-type free radicals by breaking the Si-O bond, and these free radicals contribute to the ring-opening reaction of FEC to generate TMS-modified fluoropolymers. This polymer not only reduces the generation of hydrofluoric acid (HF), reduces corrosion to the positive electrode material, and inhibits the dissolution of manganese (Mn) or cobalt (Co) ions, thereby improving the stability of the positive electrode material and reducing capacity loss, but also reduces the catalytic effect of the dissolved metal ions on the decomposition of the electrolyte in the electrochemical reaction. At the same time, due to the introduction of fluorine elements, the fluoropolymer improves the conformation of the polymer, forming a head-to-tail bonded polyvinyl fluoride, which can improve the flexibility and ionic conductivity of the interface film and help form a stable solid electrolyte interface (SEI). In addition, when the TMS group is broken, the fluorophosphate part can react with lithium ions (Li +) reaction to form fluorophosphate, which can improve the composition of SEI film, enhance the lithium ion transmission capacity, reduce the interface impedance, and enhance the stability of the interface film.
[0042] In general, the use of fluoroethylene carbonate in combination with the compound shown in Formula I can produce a synergistic effect, which enhances the ionic conductivity of the inorganic and organic components in the battery interface film, and at the same time improves the stability of the interface film under high voltage and high temperature environments. This synergistic effect reduces the decomposition of the electrolyte, reduces the interface impedance inside the battery, and protects the stability of the positive electrode material, thereby improving the cycle performance and high temperature storage performance of the battery under high voltage conditions, and the operating voltage can reach no less than 4.5V, for example, 4.5V, 4.6V, 4.7V, 4.8V, 4.9V, 5.0V.
[0043] According to an embodiment of the present application, the compound represented by Formula I includes at least one of the compounds having structures represented by Formulas 1 to 9:
[0044]
[0045]
[0046] Under high voltage conditions, the compound represented by the above formula I can effectively reduce the impedance of the battery interface, improve the stability, flexibility and ionic conductivity of the interface, reduce the decomposition of the electrolyte and the generation of hydrofluoric acid (HF), thereby reducing the corrosion of the positive electrode material, improving its stability, and reducing the capacity loss caused by material corrosion, thereby better improving the cycle performance and high-temperature storage performance of the battery.
[0047] According to an embodiment of the present application, based on the total mass of the electrolyte, the mass proportion of the second component is 0.5% to 3%, for example, it can be 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%. The content of the compound shown in Formula I meets the above conditions, which helps to form a more stable and flexible interface film on the surface of the positive and negative electrodes of the battery, which can not only reduce the interface impedance and improve the ionic conductivity of the battery, but also effectively protect the electrode material and reduce the capacity loss caused by the decomposition of the electrolyte and the dissolution of metal ions. Furthermore, the compound shown in Formula I can reduce the decomposition of the electrolyte at high voltage, inhibit the generation of HF, thereby reducing the corrosion of the internal components of the battery and improving the thermal stability and safety of the battery. As a result, the battery can further maintain excellent performance under high temperature and high voltage conditions.
[0048] According to an embodiment of the present application, the battery further includes: a positive electrode plate, the positive electrode plate includes a positive electrode active material, and the positive electrode active material includes lithium cobalt oxide (LiCoO2).
[0049] According to an embodiment of the present application, based on the total mass of the electrolyte, the mass proportion of the first component is 2% to 10%, for example, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%. In the lithium cobalt oxide system, the content of the first component meets the above conditions and can form a stable interface film rich in LiF on the positive electrode surface of the battery. The interface film can effectively reduce the interface impedance of the battery and improve the cycle stability and high temperature performance of the battery at high voltage.
[0050] According to an embodiment of the present application, based on the total mass of the electrolyte, the mass proportion of the second component is 0.5% to 3%, for example, it can be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%. In the lithium cobalt oxide system, the content of the compound shown in Formula I meets the above conditions, which helps to form a more stable and flexible interface film on the surface of the positive and negative electrodes of the battery, which can not only reduce the interface impedance and improve the ionic conductivity of the battery, but also effectively protect the electrode material and reduce the capacity loss caused by electrolyte decomposition and metal ion dissolution. Furthermore, the compound shown in Formula I can reduce the decomposition of the electrolyte at high voltage, inhibit the generation of HF, thereby reducing the corrosion of the internal components of the battery and improving the thermal stability and safety of the battery. As a result, the battery can further maintain excellent performance under high temperature and high voltage conditions.
[0051] According to an embodiment of the present application, the mass ratio of the first component to the second component is (0.67-20):1, for example, it can be 0.67:1, 1:1, 5:1, 10:1, 15:1, 20:1. The mass ratio of the first component to the second component satisfies the above conditions, which helps to further improve the stability, flexibility and ion conductivity of the interface film under high voltage and high temperature environment, reduce the interface impedance, and better reduce the decomposition of the electrolyte and the generation of hydrofluoric acid (HF), thereby reducing the corrosion of the positive electrode material, improving its stability, and reducing the capacity loss caused by material corrosion, and better improving the cycle performance and high temperature storage performance of the battery.
[0052] According to an embodiment of the present application, the electrolyte includes a non-aqueous organic solvent; the non-aqueous organic solvent includes at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate and ethyl butyrate. In the lithium cobalt oxide system, the non-aqueous organic solvent can ensure the pressure resistance of the electrolyte and also enable the electrolyte to achieve excellent dynamic performance.
[0053] According to an embodiment of the present application, based on the total mass of the electrolyte, the mass proportion of the non-aqueous solvent is 67% to 89.5%, for example, 67%, 70%, 75%, 80%, 85%, 89.5%. Therefore, in the lithium cobalt oxide system, the non-aqueous solvent meets the above conditions, which can ensure the pressure resistance of the electrolyte and also enable the electrolyte to achieve excellent dynamic performance.
[0054] According to an embodiment of the present application, the battery further comprises: a positive electrode plate, the positive electrode plate comprises a positive electrode active material, and the positive electrode active material comprises lithium nickel manganese oxide. Exemplarily, the lithium nickel manganese oxide is spinel lithium nickel manganese oxide LiNi 0.5 Mn 1.5 O4.
[0055] According to an embodiment of the present application, the positive electrode active material includes nickel manganese oxide lithium, and the operating voltage of the battery is not less than 4.7 V, for example, it can be 4.7 V, 4.75 V, 4.80 V, 4.85 V, 4.90 V, 5.0 V. In the nickel manganese oxide lithium system, the battery of the present application has a higher pressure resistance, and still has better cycle stability and high temperature storage performance under the above high pressure conditions.
[0056] According to an embodiment of the present application, based on the total mass of the electrolyte, the mass proportion of the first component is 6% to 30%, for example, it can be 6%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 24%, 25%, 26%, 28%, 30%, preferably 10% to 20%. In the nickel manganese oxide lithium system, the content of the first component meets the above conditions and can form a stable interface film rich in LiF on the positive electrode surface of the battery. The interface film can effectively reduce the interface impedance of the battery and improve the cycle stability and high temperature performance of the battery at high voltage.
[0057] According to an embodiment of the present application, based on the total mass of the electrolyte, the mass proportion of the second component is 0.5% to 3%, for example, it can be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%. In the nickel manganese oxide system, the content of the compound shown in Formula I meets the above conditions, which helps to form a more stable and flexible interface film on the surface of the positive and negative electrodes of the battery, which can not only reduce the interface impedance and improve the ionic conductivity of the battery, but also effectively protect the electrode material and reduce the capacity loss caused by electrolyte decomposition and metal ion dissolution. Furthermore, the compound shown in Formula I can reduce the decomposition of the electrolyte at high voltage, inhibit the generation of HF, thereby reducing the corrosion of the internal components of the battery and improving the thermal stability and safety of the battery. As a result, the battery can further maintain excellent performance under high temperature and high voltage conditions.
[0058] According to an embodiment of the present application, the mass ratio of the first component to the second component is (2-60): 1, for example, it can be 2: 1, 5: 1, 10: 1, 15: 1, 20: 1, 25: 1, 30: 1, 35: 1, 40: 1, 45: 1, 50: 1, 55: 1, 60: 1. The mass ratio of the first component to the second component meets the above conditions, which helps to further improve the stability, flexibility and ion conductivity of the interface film under high voltage and high temperature environment, reduce the interface impedance, better reduce the decomposition of the electrolyte and the generation of hydrofluoric acid (HF), thereby reducing the corrosion of the positive electrode material, improving its stability, and reducing the capacity loss caused by material corrosion, and better improving the cycle performance and high temperature storage performance of the battery.
[0059] According to an embodiment of the present application, the electrolyte includes a non-aqueous organic solvent; the non-aqueous organic solvent includes at least one of bisfluorocarbonate vinyl ester, 4-difluoromethylethylene carbonate, 4-trifluoromethylethylene carbonate, 2-fluoroethylmethyl carbonate, 2,2-difluoroethylmethyl carbonate, 2,2,2-trifluoroethylmethyl carbonate, 2-fluoroethylethyl carbonate, 2,2-difluoroethylethyl carbonate, 2,2,2-trifluoroethylethyl carbonate, bis(2-fluoroethyl)carbonate, bis(2,2-difluoroethyl)carbonate and bis(2,2,2-trifluoroethyl)carbonate. In the lithium nickel manganese oxide system, the above non-aqueous organic solvent can ensure the pressure resistance of the electrolyte, and also enable the electrolyte to achieve excellent dynamic performance.
[0060] According to an embodiment of the present application, based on the total mass of the electrolyte, the mass proportion of the non-aqueous solvent is 47% to 85.5%, for example, it can be 47%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 85.5%. Therefore, in the lithium nickel manganese oxide system, the non-aqueous solvent meets the above conditions, which can ensure the pressure resistance of the electrolyte and also enable the electrolyte to achieve excellent dynamic performance.
[0061] According to an embodiment of the present application, the electrolyte further includes: an electrolyte salt, based on the total mass of the electrolyte, the mass proportion of the electrolyte salt is 8% to 20%, for example, it can be 8%, 10%, 12%, 15%, 18%, 20%. As a result, the electrolyte salt meets the above conditions, and the ions in the electrolyte migrate efficiently and are stably transmitted, thereby improving the charge and discharge efficiency and power density of the battery. In addition, it helps to maintain the chemical stability of the electrolyte and reduce side reactions during high-voltage charging, such as decomposition of the electrolyte and generation of gas, which helps to extend the cycle life of the battery and improve its safety.
[0062] In some embodiments, the electrolyte salt may include at least one of LiPF6, LiAsF6, LiClO4, LiB(C2O4)2, LiBF2C2O4, LiN(SO2F)2, LiN(SO2CF3)2, LiPO2F2, LiPF2(C2O4)2, and LiPF4C2O4.
[0063] According to an embodiment of the present application, the positive electrode plate includes a positive electrode collector and a positive electrode active material layer coated on at least one side surface of the positive electrode collector, and the positive electrode active material layer includes the positive electrode active material.
[0064] According to an embodiment of the present application, the positive electrode current collector may include a metal foil or a composite positive electrode current collector. For example, the metal foil may be aluminum foil. The composite positive electrode current collector may include a polymer material base and a metal layer formed on at least one side of the surface of the polymer material base. For example, the composite negative electrode current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT) and other substrates).
[0065] According to an embodiment of the present application, the positive electrode active material layer may further optionally include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0066] According to an embodiment of the present application, the positive electrode active material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0067] According to the embodiments of the present application, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, and the binder are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0068] According to an embodiment of the present application, the battery further includes: a negative electrode plate; the negative electrode plate includes a negative electrode active material layer, and the negative electrode active material layer includes a binder.
[0069] According to an embodiment of the present application, the binder may include at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0070] According to an embodiment of the present application, the negative electrode active material may adopt a negative electrode active material for a battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: soft carbon, hard carbon, silicon-based material, tin-based material, etc., and the soft carbon includes graphite. The silicon-based material may include at least one of elemental silicon, silicon oxide compound, silicon carbon composite, silicon nitrogen composite and silicon alloy. The tin-based material may include at least one of elemental tin, tin oxide compound and tin alloy.
[0071] According to an embodiment of the present application, the negative electrode active material layer may further include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0072] According to an embodiment of the present application, the negative electrode active material layer may optionally further include other auxiliary agents, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0073] According to an embodiment of the present application, the negative electrode plate includes a negative electrode current collector, and the negative electrode active material layer is disposed on at least one side surface of the negative electrode current collector.
[0074] According to an embodiment of the present application, the negative electrode current collector may be a metal foil or a composite current collector. For example, aluminum or copper foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (aluminum, copper, copper alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.).
[0075] According to an embodiment of the present application, a negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, a negative electrode sheet can be obtained.
[0076] According to an embodiment of the present application, the battery further includes a separator, which is disposed between the positive electrode sheet and the negative electrode sheet, and mainly plays a role in preventing the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0077] The present application has no particular limitation on the type of isolation membrane, and any known porous isolation membrane with good chemical stability and mechanical stability can be selected.
[0078] According to an embodiment of the present application, the material of the isolation membrane may include one or more of polyolefin, aromatic polyamide, polytetrafluoroethylene, and polyethersulfone. Further, the isolation membrane includes one or both of polyethylene and polypropylene. In addition, the diaphragm may be obtained by stacking multiple layers of materials in sequence, for example, the isolation membrane includes a polypropylene layer, a polyethylene layer, and a polypropylene layer stacked in sequence.
[0079] According to an embodiment of the present application, the thickness of the isolation film may be 6 μm-16 μm, for example, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, etc.
[0080] The scheme of the present application will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the literature in this area or the product specification are carried out. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.
[0081] Example 1 (LNMO system)
[0082] 1. The electrolyte provided in this embodiment includes, by weight percentage, 13% lithium salt main salt, 6% fluoroethylene carbonate (FEC), 1% compound of formula 1, and the organic solvent is supplemented to 100%, based on the total weight of the electrolyte. The lithium salt main salt includes lithium hexafluorophosphate (LiPF6), and the organic solvent is 2,2,2-trifluoroethyl methyl carbonate (FEMC).
[0083] The steps for preparing the electrolyte are as follows:
[0084] In a glove box filled with nitrogen, the solvents FEC and FEMC were first mixed evenly, 86 g of the mixed solution was taken, 13 g of LiPF6 was slowly added to the mixed solvent, and 1 g of the compound of formula 1 was added while stirring until it was completely dissolved, and then the mixture was mixed evenly to obtain a lithium-ion battery electrolyte.
[0085] 2. The positive electrode active material lithium nickel manganese oxide powder, the conductive agent acetylene black, carbon nanotubes and polyvinylidene fluoride (PVDF) are dispersed in the solvent NMP according to a mass ratio of 94:2.5:1.5:2, and the solid content is 63% to obtain a positive electrode active material layer slurry; the positive electrode active material layer slurry is evenly coated on the surface of the positive electrode collector aluminum foil, and the positive electrode sheet is obtained after drying, rolling, baking, slitting and spot welding of the pole ears. The total thickness of the positive electrode sheet is 116μm.
[0086] 3. Disperse the negative electrode active material graphite, the conductive agent conductive carbon black super p, the binder SBR, and the dispersant CMC in deionized water at a mass ratio of 94.5:2:2:1.5, and stir evenly to obtain a negative electrode active material layer slurry; evenly coat the negative electrode active material layer slurry on the surface of the negative electrode collector copper foil, and obtain a negative electrode sheet after drying, rolling, baking, slitting and spot welding the pole ears. The total thickness of the negative electrode sheet is 108 μm.
[0087] 4. Stack the prepared positive electrode sheet, negative electrode sheet and 12μm three-layer separator in order, place the separator between the positive electrode sheet and the negative electrode sheet, put the battery cell into an aluminum-plastic film packaging bag after stacking, and vacuum bake it at 75°C for 48h to obtain the battery cell to be filled with liquid, and then inject the above-mentioned electrolyte into the battery cell in a glove box. After packaging, formation, aging, and capacity separation, the preparation of the lithium-ion battery is completed, and the design capacity is 1300mAh.
[0088] The preparation methods of Examples 2-8, 14-22, 25-29 and Comparative Examples 1-3 are the same as those of Example 1, and the differences are detailed in Table 1. The difference between Example 22 and Example 21 is that the second additive is changed to Compound 1 and Compound 2 in a mass ratio of 0.5:0.5.
[0089] Example 9 (LCO system)
[0090] 1. The electrolyte provided in this embodiment includes, by mass percentage, 15% LiPF6 lithium salt, 2% fluoroethylene carbonate (FEC), other additives (2% succinonitrile + 1% 1,2-bis(cyanoethoxy)ethane + 2% hexanetrinitrile + 4% 1,3-propane sultone), 1% compound of formula 1, and an organic solvent (ethylene carbonate: propylene carbonate: ethyl methyl carbonate: propyl propionate = 15:10:20:55) supplemented to 100%, based on the total mass of the electrolyte.
[0091] The steps for preparing the electrolyte are as follows:
[0092] In a glove box filled with nitrogen, the solvents EC:PC:EMC:PP were first mixed uniformly in a mass ratio of 15:10:20:55, 73 g of the mixed solution was taken, 2 g of succinonitrile, 1 g of 1,2-bis(cyanoethoxy)ethane, 2 g of hexanetrinitrile, 4 g of 1,3-propane sultone and 15 g of LiPF6 were slowly added to the mixed solvent, and 2 g of FEC and 1 g of the compound of formula 1 were added while stirring until completely dissolved, and then the mixture was uniformly mixed to obtain a lithium-ion battery electrolyte.
[0093] 2. The positive electrode active material lithium cobalt oxide powder, the conductive agent acetylene black and polyvinylidene fluoride (PVDF) are dispersed in the solvent NMP according to the mass ratio of 97.3:1.5:1.2, and the solid content is 68% to obtain the positive electrode active material layer slurry; the positive electrode active material layer slurry is evenly coated on the surface of the positive electrode collector aluminum foil, and the positive electrode sheet is obtained after drying, rolling, baking, slitting and spot welding of the pole ears. The total thickness of the positive electrode sheet is 96μm.
[0094] 3. Disperse the negative electrode active material graphite, the conductive agent conductive carbon black super p, the binder SBR, and the dispersant CMC in deionized water in a mass ratio of 95:1.5:2:1.5, and stir evenly to obtain the negative electrode active material layer slurry; evenly coat the negative electrode active material layer slurry on the surface of the negative electrode collector copper foil, and obtain the negative electrode sheet after drying, rolling, baking, slitting and spot welding the pole ear. The total thickness of the negative electrode sheet is 135 μm.
[0095] 4. Stack the prepared positive electrode sheet, negative electrode sheet and 12μm three-layer separator in order, place the separator between the positive electrode sheet and the negative electrode sheet, put the battery cell into an aluminum-plastic film packaging bag after stacking, and vacuum bake it at 75°C for 48h to obtain the battery cell to be injected with liquid, and then inject the above electrolyte into the battery cell in a glove box. After packaging, formation, aging and capacity separation, the preparation of the lithium-ion battery is completed, and the design capacity is 1750mAh.
[0096] The preparation methods of Examples 10-13, 23-24 and 30-33 are the same as those of Example 9, and the differences are detailed in Table 1.
[0097] The electrolyte of Comparative Example 1 does not contain the compound represented by Formula I.
[0098] The electrolyte of Comparative Example 2 does not contain fluoroethylene carbonate.
[0099] The compound represented by formula I in Comparative Example 3 is tris(trimethylsilyl)phosphate (TMSP).
[0100] Test example (LNMO system)
[0101] The lithium ion batteries prepared in Examples 1 to 8, 14 to 22, 25 to 29 and Comparative Examples 1 to 3 were respectively subjected to impedance, cycle and high temperature performance tests. The test methods are as follows. The test results are shown in Table 1:
[0102] 1. Normal temperature cycle performance test:
[0103] The battery was charged at room temperature (25°C) at a constant current of 0.5C to 4.85V, and at a constant voltage of 4.85V to a cut-off current of 0.05C. The battery was then discharged at 0.5C to a voltage of 3.5V. The charge and discharge were repeated for X1 weeks. The discharge capacity of the X1th cycle was recorded and divided by the discharge capacity of the 1st cycle to obtain the capacity retention rate. When the capacity retention rate was 80%, the corresponding number of weeks was recorded, which was the normal temperature cycle life X1.
[0104] 2. High temperature cycle performance test:
[0105] The battery was charged at a high temperature of 45°C at a constant current of 0.5C to 4.85V, and at a constant voltage of 4.85V to a cut-off current of 0.05C, and then discharged at 0.5C. The charge and discharge were repeated. The discharge capacity of the X2th cycle was recorded and divided by the discharge capacity of the 1st cycle to obtain the capacity retention rate. When the capacity retention rate was 80%, the corresponding number of weeks was recorded, which was the high temperature cycle life X2.
[0106] 3. High temperature storage performance test:
[0107] The battery was charged to 4.85V at 0.5C constant current at room temperature 25℃, charged to a cut-off current of 0.05C at a constant voltage of 4.85V, and then discharged at a constant current of 0.5C, and the discharge capacity was recorded as C2. At room temperature 25℃, the battery was charged to 4.85V at 0.5C constant current, charged to a cut-off current of 0.05C at a constant voltage of 4.85V, and then the battery was transferred to a high temperature of 60℃ and left for 14 days, and then discharged at a constant current of 0.5C, and the discharge capacity was recorded as C3, and the 60℃ capacity retention rate = C3 / C2*100%.
[0108] 4. DC resistance DCR test:
[0109] Place the battery in a 25℃ environment, discharge at 0.5C constant current to a cut-off voltage of 3.5V, let stand for 5 minutes, charge at 0.5C constant current and constant voltage to an upper limit voltage of 4.85V, with a cut-off current of 0.05C, and then discharge at 0.5C constant current for 60 minutes. Place the battery adjusted to 50% SOC at 25℃, let stand for 5 minutes, and discharge at 2C constant current for 10 seconds. The discharge current during 2C discharge is I2C. Record the initial voltage V0 and the voltage V1 after 10 seconds of discharge. The discharge DC internal resistance calculation formula at 50% SOC is as follows: DCR (mΩ) = (V0-V1) / I2C×1000.
[0110] Test example (LCO system)
[0111] The lithium ion batteries prepared in Examples 9 to 13, 23 to 24 and 30 to 33 were tested for impedance, cycle and high temperature performance respectively. The test methods are as follows. The test results are shown in Table 1:
[0112] 1. Normal temperature cycle performance test:
[0113] The battery was charged at room temperature 25°C at a constant current of 1C to 4.53V, and at a constant voltage of 4.53V to a cut-off current of 0.05C. The battery was then discharged at 1C to a voltage of 3.0V. The charge and discharge were repeated for X1 weeks. The discharge capacity of the X1th cycle was recorded and divided by the discharge capacity of the 1st cycle to obtain the capacity retention rate. When the capacity retention rate was 80%, the corresponding number of weeks was recorded, which was the normal temperature cycle life X1.
[0114] 2. High temperature cycle performance test:
[0115] The battery was charged at a high temperature of 45°C at a constant current of 1C to 4.53V, and then at a constant voltage of 4.53V to a cut-off current of 0.05C. The battery was then discharged at 1C, and the charge and discharge were repeated. The discharge capacity of the X2th cycle was recorded and divided by the discharge capacity of the 1st cycle to obtain the capacity retention rate. When the capacity retention rate was 80%, the corresponding number of weeks was recorded, which was the high temperature cycle life X2.
[0116] 3. High temperature storage performance test:
[0117] The battery was charged to 4.53V at 1C constant current at room temperature 25°C, charged to a cut-off current of 0.05C at a constant voltage of 4.53V, and then discharged at a constant current of 1C, and the discharge capacity was recorded as C2. At room temperature 25°C, the battery was charged to 4.53V at 1C constant current, charged to a cut-off current of 0.05C at a constant voltage of 4.53V, and then the battery was transferred to a high temperature of 60°C for 14 days, and then discharged at a constant current of 1C, and the discharge capacity was recorded as C3, and the 60°C capacity retention rate = C3 / C2*100%.
[0118] 4. DC resistance DCR test:
[0119] Place the battery in a 25℃ environment, discharge at 1C constant current to a cut-off voltage of 3.0V, let stand for 5min, charge at 1C constant current and constant voltage to an upper limit voltage of 4.53V, with a cut-off current of 0.05C, and then discharge at 1C constant current for 30min. Place the battery adjusted to 50% SOC at 25℃, let stand for 5min, and discharge at 2C constant current for 10s. The discharge current during 2C discharge is I2C. Record the initial voltage V0 and the voltage V1 after 10s of discharge. The discharge DC internal resistance calculation formula at 50% SOC is as follows: DCR (mΩ) = (V0-V1) / I2C×1000.
[0120]
[0121]
[0122]
[0123]
[0124] The results are shown in Table 1, and it can be seen that the battery performance of Examples 1 to 33 is better than that of Comparative Examples 1 to 3 as a whole. This shows that FEC and the compound shown in Formula I act synergistically to enhance the ionic conductivity of the inorganic and organic components in the battery interface film, while improving the stability of the interface film under high voltage and high temperature environments. This synergistic effect reduces the decomposition of the electrolyte, reduces the interfacial impedance inside the battery, and protects the stability of the positive electrode material, thereby improving the battery's cycle performance and high-temperature storage performance under high-voltage conditions. In Comparative Example 2, only Compound 1 was added to the electrolyte as the second additive, and the first additive FEC was not contained. The solvent was only FEMC, and the dielectric constant corresponding to FEMC was much lower than that of FEC, and the dissociation ability of the lithium salt was weak, resulting in a low conductivity of the electrolyte and the inability of the battery cell to charge and discharge normally.
[0125] It can be seen from Examples 1-8 that in the nickel manganese oxide lithium system, when the mass proportion of the first component is 6% to 30%, a stable interface film rich in LiF can be formed on the positive electrode surface of the battery, which can effectively reduce the interfacial impedance of the battery and improve the cycle stability and high temperature performance of the battery under high voltage. If the mass proportion of the first component is too low, the impedance is too large, and the normal temperature cycle attenuation will deteriorate; if the mass proportion of the first component is too high, the gas production is too high, the viscosity is too high, and the cycle performance and high temperature performance are too low. Among them, the mass proportion of the first component is 10% to 20%, and the overall performance of the battery is better.
[0126] It can be seen from Examples 9-13 that in the lithium cobalt oxide system, the mass proportion of the first component is 2% to 10%, which can form a stable interface film rich in LiF on the surface of the battery electrode. The interface film can effectively reduce the interfacial impedance of the battery and improve the cycle stability and high temperature performance of the battery at high voltage.
[0127] It can be seen from Examples 1 and 25-33 that the mass proportion of the second component is 0.5% to 3%, which helps to form a more stable and flexible interface film on the surface of the positive and negative electrodes of the battery, which can not only reduce the interface impedance and improve the ionic conductivity of the battery, but also effectively protect the electrode material and reduce the capacity loss caused by the decomposition of the electrolyte and the dissolution of metal ions. Furthermore, the compound shown in Formula I can reduce the decomposition of the electrolyte at high voltage, inhibit the generation of HF, thereby reducing the corrosion of the internal components of the battery, and improving the thermal stability and safety of the battery. As a result, the battery can further maintain excellent performance under high temperature and high voltage conditions. The Si-O bond of the silane group in the compound shown in Formula I breaks and releases trimethylsilane (TMS) free radicals. If the mass proportion of the first component is too high, the silane group will combine with F- in the electrolyte to generate low-boiling fluorosilane, which will cause more gas production. If the mass proportion of the first component is too low, the stability of the SEI film will be low, the capacity loss will be too high, and the cycle performance and high temperature performance will be low.
[0128] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A battery, characterized in that: The operating voltage of the battery is not less than 4.5V, and the battery comprises an electrolyte, wherein the electrolyte comprises a first component and a second component; The first component includes fluoroethylene carbonate; The second component includes a compound shown in formula I: wherein R1, R2 and R3 are each independently selected from F, C1-C4 alkyl, C2-C4 alkenyl, -OP(=O)F2, -Si(R3)(R4)OP(=O)F2 or -OSi(R3)(R4)OP(=O)F2; R3 and R4 are each independently selected from C1-C4 alkyl groups.
2. The battery according to claim 1, characterized in that The compound represented by Formula I includes at least one of the compounds having structures represented by Formulas 1 to 9:
3. The battery according to claim 1, characterized in that Based on the total mass of the electrolyte, the mass proportion of the second component is 0.5% to 3%.
4. The battery according to any one of claims 1 to 3, characterized in that: Further including: A positive electrode plate, wherein the positive electrode plate comprises a positive electrode active material, wherein the positive electrode active material comprises lithium cobalt oxide.
5. The battery according to claim 4, characterized in that Based on the total mass of the electrolyte, the mass proportion of the first component is 2% to 10%; And / or, the mass ratio of the first component to the second component is (0.67-20):
1.
6. The battery according to claim 4, characterized in that The electrolyte includes a non-aqueous organic solvent; The non-aqueous organic solvent comprises at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate and ethyl butyrate; And / or, based on the total mass of the electrolyte, the mass proportion of the non-aqueous solvent is 67% to 89.5%.
7. The battery according to claims 1 to 3, characterized in that: Further including: A positive electrode plate includes a positive electrode active material, and the positive electrode active material includes lithium nickel manganese oxide.
8. The battery according to claim 7, characterized in that The operating voltage of the battery is not less than 4.7V.
9. The battery according to claim 7, characterized in that Based on the total mass of the electrolyte, the mass proportion of the first component is 6% to 30%, preferably 10% to 20%; And / or, the mass ratio of the first component to the second component is (2-60):
1.
10. The battery according to claim 7, characterized in that The electrolyte includes a non-aqueous organic solvent; The non-aqueous organic solvent comprises at least one of bisfluoroethylene carbonate, 4-difluoromethylethylene carbonate, 4-trifluoromethylethylene carbonate, 2-fluoroethyl methyl carbonate, 2,2-difluoroethyl methyl carbonate, 2,2,2-trifluoroethyl methyl carbonate, 2-fluoroethyl ethyl carbonate, 2,2-difluoroethyl ethyl carbonate, 2,2,2-trifluoroethyl ethyl carbonate, bis(2-fluoroethyl) carbonate, bis(2,2-difluoroethyl) carbonate and bis(2,2,2-trifluoroethyl) carbonate; And / or, based on the total mass of the electrolyte, the mass proportion of the non-aqueous solvent is 47% to 85.5%.
11. The battery according to claim 1, characterized in that The electrolyte further includes an electrolyte salt, and the content of the electrolyte salt is 8% to 20% based on the total mass of the electrolyte.
Citation Information
Patent Citations
Lithium ion battery electrolyte applicable to silicon carbon negative electrode and resistant to high voltage
CN106848399A
Electrolyte additive for lithium secondary battery, electrolyte for lithium secondary battery comprising same, and lithium secondary battery
CN114402468A
Lithium ion battery electrolyte and lithium ion battery thereof
CN115548442A
Lithium secondary battery
KR1020160030765A
KR20240018202A